An outbreak of early syphilis: cases from North Manchester General Hospital. Issue 5 (1st October 2001) - Lacey, H B; Higgins, S P; Graham, D
Abstract : Objectives: To describe the features of an outbreak of early syphilis in North Manchester. Methods: Retrospective KC60 and case note review. Results: In a 25 month period, 10 cases of primary, 22 of secondary, and nine cases of early latent syphilis were diagnosed. 39 were homosexual or bisexual men, 20 being co-infected with HIV. Most infections were acquired locally and in 19/41 cases oral sex was the only risk factor. High rates of unprotected anal sex were reported among the homosexual men and co-infection with other STIs was common. Conclusion: This outbreak will facilitate the spread of HIV in the homosexual male population. Unsafe sexual practice is common and the perception that oral sex is "safe" needs revisiting. Delays in accessing GUM clinic appointments must be addressed as part of the control strategy.